A variable twist blade concept for more effective wind generation: design and realization. Issue 2 (2nd April 2016) - Gili, Piero; Frulla, Giacomo
Abstract: The increasing utilization of green resources is driving research toward the design and development of new and more efficient energy harvesting systems. As far as the wind energy sector is concerned, aerodynamic design and the definition of new airfoils, specifically devoted to the application of wind rotors, has given a huge impulse in this direction. However, the rigid blade concept is still an important constraint in energy extraction during off-design conditions or start-up phases. In order to cope with this problem, a new system has been developed and manufactured within the specifically funded VENTURAS® (VENTo: Una Risorsa Altamente Sfruttabile or 'wind: a highly exploitable resource') Project. The new system applies morphing to modify blade twisting along the blade span (modifying the pitch angle of some sections) while maintaining the same chord distribution as the design configuration. This innovation offers the possibility of partially adapting the blade configuration to the operating point, thus improving rotor efficiency. Design details mechanisms and deformable skin are discussed. Application to small/–micro wind turbines seems the most promising field for such equipment, but its extension to different fields (such as UAV morphing wings) could be of a certain interest as far as energy saving is concerned. Graphical abstract: